Unveiling Oral Cancer Epidemiology in Pakistan: Insights From a Case–Control Study - Arifa Shabir; Sara Kazmi; Muhammad Usman Rashid; Iqra Mubeen; Arif Jamshed; Syed Raza Hussain; Naila Malkani (Global Health, Epidemiology and Genomics)
Conclusion: The study underscores the elevated prevalence of OC among Pakistani men, attributable in part to lower literacy rates and inadequate access to healthcare facilities. The implementation of targeted prevention strategies informed by these epidemiological insights is essential for mitigating the burden of OC in the region.